Photoacoustic Imaging Probes Based on Tetrapyrroles and Related Compounds - Jean Michel Merkes (International Journal of Molecular Sciences, 2020)
Photoacoustic imaging (PAI) is a rapidly evolving field in molecular imaging that enables imaging in the depths of ultrasound and with the sensitivity of optical modalities. PAI bases on the photoexcitation of a chromophore, which converts the absorbed light into thermal energy, causing an acoustic pressure wave that can be captured with ultrasound transducers, in generating an image. For in vivo imaging, chromophores strongly absorbing in the near-infrared range (NIR; > 680 nm) are required. As tetrapyrroles have a long history in biomedical applications, novel tetrapyrroles and inspired mimics have been pursued as potentially suitable contrast agents for PAI. The goal of this review is to summarize the current state of the art in PAI applications using tetrapyrroles and related macrocycles inspired by it, highlighting those compounds exhibiting strong NIR-absorption. Furthermore, we discuss the current developments of other absorbers for in vivo photoacoustic (PA) applications.